The Relationship between Energy Consumption and Economic Growth: Evidence from Azerbaijan - Mukhtarov, Shahriyar; Mikayilov, Jeyhun I.; İsmayılov, Vüqar (International Journal of Energy Economics and Policy, 2017)
The study investigates the causal relationship between energy consumption and economic growth in Azerbaijan using annual data covering the period from 1990 to 2015. We used Toda-Yamamoto causality test framework of vector autoregressive (VAR) model to test causal relationship between the variables. The results of this test show that there is bidirectional causality between energy consumption and economic growth. Findings of the study might be useful tool for the similar economies to give appropriate energy related policy decisions. Keywords: energy consumption, economic growth, Toda-Yamamoto causality test, Azerbaijan JEL Classifications: C22, Q43, Q48